Use of Content Management Services By Using Audio Visual Media For Improving Speaking Skills In Students of MTS Negeri 2 Medan - Fikri Nurhuda Dinul; Gusman Lesmana (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
This study aims to determine the level of significance of the influence of content mastery services on improving speaking skills in class VIII students of MTs Negeri 2 Medan Dormitory. The research respondents were students of the Dormitory of MTs Negeri 2 Medan with the research sample taken using purposive sampling technique so that there were 16 students who had problems with lack of speaking skills who were then given content mastery services using audio-visual media. The results of this study indicate that (1) There is a significant effect of content mastery services using audio-visual media on students' speaking skills which is indicated by the magnitude of the results of the hypothesis test obtained t_count = 3.193 and t_table = 2.04 so that the results obtained t_countt_table (3,193 2, 04) with a correlation coefficient of -3.193 which indicates a positive influence. the average score of improving students' speaking ability in the control group was 77.75, while the speaking ability of students in the experimental group obtained an average score of 83.6, which means that there was a significant difference in scores